Impacts of climatic variability on rainwater tank outcomes for an inland city, Canberra. (1st January 2014) - Imteaz, Monzur A.; Matos, Cristina; Shanableh, Abdallah
A daily water balance model is used for the performance analysis and design optimisation of household rainwater tank for an inland Australian city, Canberra. To investigate the climatic variabilities of rainwater tank outcomes nine representative years (three for each dry, average and wet condition) are selected from historical rainfall data. For the three climatic conditions, a number of rainwater tank outcomes (water savings, townwater augmentation, overflow and reliability) are presented in relations to tank volume, roof area, number of people in a house (i.e., water demand). It is found that 100% reliability cannot be achieved even in wet year with a large tank (10, 000 L) connected with a large roof (300 m 2 ). Also, it is observed that significant climatic variabilities exist in regards to studied rainwater tank outcomes, except for very few conditions having very large tank (10, 000 L) connected with a small roof (100 m 2 ). However, computed variabilities are still lower than the expected climatic variabilities in regards to annual water savings, annual townwater uses and reliabilities computed for Australian coastal cities, i.e., Sydney and Melbourne.